Effect of Salt Content on Biogas Production and Microbial Activity: Review Study - Alhraishawi, Ali; Aslan, Sukru (European Scientific Journal, ESJ, 2023)
Over the years, biogas production technology has advanced with the goal of reducing process costs and greenhouse gas emissions, and increasing biogas production. Several design factors and operational aspects must be taken into account in order to produce a stable and efficient biogas. When the substrates contain high salts, anaerobic treatment will be ineffective due to the disadvantages of high energy input and operating cost, membrane contamination, and low efficiency. This indicates that the treatment of high salinity organic waste is a big challenge. High salinity levels had a negative effect on bacterial growth through bacterial osmotic pressure metabolism. For example, high salinity can alter the course of fermentation and the accumulation of volatile fatty acids at high concentrations, as well as cause a decrease in methane yield and maximum rate of methane production, prolonging the late-stage period. A low level of salt concentration encourages the growth of bacteria since sodium is essential for the growth and metabolism of microorganisms in AD systems. When the sodium salt concentration is less than 8 g/L, there is no significant inhibition in the generation of methane. Addition of >8 g/L NaCl, however, significantly reduced methane production (causing 17-80 percent inhibition). This paper focuses on understanding in detail how NaCl affects methane production and microbial activity, report salt concentrations that improve process efficiency and reduce inhibition, as well as review the modified kinetic model and demonstrate the effect of salt on methane production and delay in methanogenesis.